La telenovela en familia, una mirada en busca de horizonte - Jorge A. González (Estudios sobre las Culturas Contemporáneas)
The family, an open system that is shaped and structured by the flux of inter and intrapersonal relationships, is the point of departure for the author´s consideration of the analysis of the soap opera in the family. As a methodological enterprise, this article shows the theoretical tools and practices utilized for the construction of the Soap opera- Family relationship. For this purpose, the principal guide is the Protocolo de Observacion Etnografica- or Protocol for Ethnographic Observation of the differential usages and modes of watching soap operas in the family (Gonzalez & Mugnaini, 1986). This work, then, places the-family within a particular physical space where practices, situations and collective and individual discourses are "objectively" generated by intercourse with the television drama; it also systematically recovers the sense of familial exposition (usages and appropriations) to the soap opera.